Novel risk loci encompassing genes influencing STAT3, GPCR, and oxidative stress signaling are associated with co-morbid GERD and COPD - Wilson, Ava C; Rocco, Alison; Chiles, Joe; Srinivasasainagendra, Vinodh; Labaki, Wassim; Meyers, Deborah; Hidalgo, Bertha; Irvin, Marguerite R; Bhatt, Surya P; Tiwari, Hemant; McDonald, Merry-Lynn (PLoS genetics, 2025)
Chronic obstructive pulmonary disease (COPD) is a leading cause of death globally. Gastroesophageal reflux disease (GERD) is a common comorbidity in COPD associated with worse pulmonary symptoms, reduced quality of life, and increased exacerbations and hospitalizations. GERD treatment in COPD is associated with a lower risk of exacerbations and mortality; however, it is not clear whether these findings can be attributed to aging populations where both diseases are likely to co-occur or reflect shared etiology. To test for the influence of common etiology in both diseases, we aimed to identify shared genetic etiology between GERD and COPD. We performed the first whole-genome sequence association analysis of comorbid GERD and COPD in 12,438 multi-ancestry participants. The co-heritability of GERD and COPD was 39.7% (h2 = 0.397, SE = 0.074) and we identified several ancestry-independent loci associated with co-morbid GERD and COPD (within LINC02493 and FRYL) known to be involved in oxidative stress and G protein-coupled receptor (GPCR) signaling mechanisms. We found several loci associated with co-morbid GERD and COPD previously associated with GERD or COPD individually, including HCG17, which plays a role in oxidative stress mechanisms. Gene set enrichment identified GPCR signaling pathways in co-morbid GERD and COPD loci. Rare variants in ZFP42, encoding key regulators of the IL6/STAT3 pathway, have been previously implicated with GI disorders and were associated with co-morbid GERD and COPD. We identified common genetic etiology for GERD in COPD which begins to provide a mechanistic foundation for the potential therapeutic utility of STAT3, oxidation, and GPCR signaling pathway modulators in both GERD and COPD.